Relación entre Inteligencia Emocional y aprendizaje significativo en niños de 6to grado del C.E.P. Nº 00536 - Rioja - Chávez Rojas, Nancy (2002)
The present investigation descriptive correlacional was carried out with students of the sixth degree of the Primary school Manuel Segundo of the Águila Velásquez of Rioja. The problem, hypothesis and general objective were structured by means of the relationship of the variable emotional intelligence and significant learning. The theoretical sustentation between emotional intelligence and their relationship with the significant learning, it has been based on the theories of Daniel Góleman's emotion and the theory of the significant learning of Ausubel. The gradualidad relacional, positive or negative, enunciated in the investigation hypothesis centers its presumption in the interactive dependence of the mental life of the educandos, product of the balance of is emotional and rational mind. Thirty educandos conformed the sample, it was used the design of correlation investigation and the statistical parameter of correlation by ranges of Spearman, the procedure consisted on the tests application to evaluate the emotional intelligence and the significant learning: with whose results the gradualidad correlacional was determined. Made the contrastación of the hypothesis the results evidence a weak positive correlation (0,23) . In consequence the conclusions settle down with rigor that educators and progenitors stimulated the emotional intelligence weakly: autoconciencia, autocontrol, motivation, empathy and social relationships . In a logic it is recommended that the one referred correlato owes potencializarse starting from a training on the kindness and purposes of the emotional intelligence .